Synthesis of biomimetic coating of hydroxyapatite by microarc oxi dation and hydrothermal treatment. - Liên, Đỗ Ngọc; Sinh, Nguyễn Văn (Vietnam Journal of Chemistry, 2012)
A biomimetic coating of hydroxyapatite (HA) was prepared on aluminium substrate by microarc oxidation (MAO) and hydrothermal treatment. The MAO method was suitable for aluminium substrate to form a ceramic coating in electrolytes of glycerophosphate (b-GP) and calcium acetate monohydrate (CA). The thin film with a Ca/P ratio equivalent to hydroxyapatite was abtained when final voltage and current density were 330 V and 0.018 A/cm2 in electrolyte containing 0.06 (b-GP) and 0.25 M (CA). The thicker film of HA was formed on the surface of film obtained by MAO after hydrothermal treatment.